2022
DOI: 10.3390/bioengineering9100532
|View full text |Cite
|
Sign up to set email alerts
|

A Novel System for Precise Grading of Glioma

Abstract: Gliomas are the most common type of primary brain tumors and one of the highest causes of mortality worldwide. Accurate grading of gliomas is of immense importance to administer proper treatment plans. In this paper, we develop a comprehensive non-invasive multimodal magnetic resonance (MR)-based computer-aided diagnostic (CAD) system to precisely differentiate between different grades of gliomas (Grades: I, II, III, and IV). A total of 99 patients with gliomas (M = 49, F = 50, age range = 1–79 years) were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, a recent study (46) has shown the superiority of segmenting tumor volume over its ellipsoidal approximation to assess tumor burden in DIPG. The fine delineation of contours will make possible to further test the impact of additional morphological features, including the histogram of oriented gradients as proposed by Alksas et al (47) for the estimation of the genomic mutations. The manual segmentation is however tedious and its reproducibility still needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study (46) has shown the superiority of segmenting tumor volume over its ellipsoidal approximation to assess tumor burden in DIPG. The fine delineation of contours will make possible to further test the impact of additional morphological features, including the histogram of oriented gradients as proposed by Alksas et al (47) for the estimation of the genomic mutations. The manual segmentation is however tedious and its reproducibility still needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…To date the application of radiomics in GM setting has shown considerable progress in demonstrating that it can be a tool capable of deriving much information, with implications in diagnostics, such as differentiating tumors based on texture analysis, differentiating treatment effects (radiation necrosis, pseudo-progression) and tumor recurrence, in prognosis such as survival stratification (1)(2)(3)(4)(34)(35)(36)(37)(38) and applications in the choice of optimal therapy (39-41), e.g., stratification of response to anti-angiogenic treatment for recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the use of medical imaging, as a non-invasive tool to derive prognostic factors that can predict outcome such as survival, PFS, and response to therapy, is becoming increasingly popular. The images can be described not only qualitatively in order to highlight the presence of necrotic, edemigenous, malignant, suspected or metabolically active areas, but also quantitatively in order to generate numbers that become real measurable data (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of molecular mutations using MRI features proved to be a useful method for diffuse LGG prediction, with the advantage of being a non-invasive procedure 15 . Alksas et al 16 proposed an imaging-based glioma grading system that uses contrast-enhanced MRI, fluid-attenuated inversion-recovery MRI, and diffusion-weighted MRI to extract morphological, textural, and functional features. Then, the optimal features given by the Gini impurity index are fed to a multi-layer perceptron (MLP) to discriminate between different grades of glioma.…”
Section: Introductionmentioning
confidence: 99%